Supramolecular Engineering of Amorphous Porous Polymers for Rapid Adsorption of Micropollutants and Solar‐Powered Volatile Organic Compounds Management (Adv. Mater. 50/2022). Issue 50 (16th December 2022) - Cho, Wansu; Lee, Dongjun; Choi, Gyeonghyeon; Kim, Jihyo; Kojo, Acquah Ebenezer; Park, Chiyoung
Abstract : Environmental Remediation In article number 2206982, Chiyoung Park and co‐workers present oxidized covalent triazine frameworks (CTFs) that show exceptional efficiency for removal of phenol derivatives from water and high efficiency for removal of volatile organic compounds via solar‐driven water evaporation. The combination of adsorption and photothermal evaporation using oxidized CTFs offers a cost‐effective and complete strategy for purification of water polluted by mixed pollutants.